Effects of cement contents on the performance of cement asphalt emulsion mixtures with rapidly developed early-age strength. (30th May 2020) - Tian, Yaogang; Lu, Dong; Ma, Ronghui; Zhang, Jun; Li, Weiguang; Yan, Xiaohui
Highlights: Cement asphalt emulsion mixtures (CAEMs) with high cement content were prepared. Frost resistance of CAEMs under multiple freeze-thaw cycles was investigated. Early-age strength and pavement performance of CAEMs were investigated. Relation between 4-h strength and pavement performance of CAEMs was developed. Abstract: This study aims to develop a new type of cement asphalt emulsion mixtures (CAEMs) by introducing high content of cement. Firstly, 4-h compressive strength and elastic modulus were adopted to evaluate the early-age strength of CAEMs. And then moisture susceptibility, high-temperature performance, frost resistance, low-temperature performance and fatigue performance were determined to characterize the pavement performance of CAEMs. Finally, the relation between 4-h compressive strength and pavement performance of CAEMs was developed. Experiment results showed that high content of cement provided a high and a rapid developed early-age strength of CAEMs. A strong linear correlation was also obtained between the early-age strength and partial pavement performance of CAEMs.